Mainstreaming Climate Change Adaptation into Rural Development Plans in Vietnam—How to Build Resilience at the Interface of Policy and Practice - Halbherr, Lucia; Maat, Harro; Talsma, Tiffany; Hutjes, Ronald (MDPI, 2021)
The interconnectedness between climate change and development has generated an increasing interest amongst development organisations to integrate adaptation into government rural development plans in a way that effectively increases resilience at a local level. However, the nature of climate change resilience is widely debated in the literature, and there is a knowledge gap regarding the best way to address adaptation at the interface with development objectives as part of mainstreaming. This paper aims to address this knowledge gap via a case study of a community-based, Climate-Smart Agriculture (CSA) project in Vietnam. A case study approach was applied with fieldwork at one project site, complemented by semi-structured interviews with government stakeholders, key experts, and project leaders of related projects. The analysis identifies five key factors that enhance rural resilience in a smallholder agricultural context: (i) engaging local governments as partners, (ii) considering broader landscape issues such as markets, (iii) providing farmers with support to facilitate adoption of CSA practices, (iv) fostering community capacity building, and (v) promoting adaptive management and scenario planning to deal with uncertainty. The paper concludes that resilience is multidimensional and not solely in line with any one of the approaches dominant in the literature.